Musculoskeletal Pain as Related to Some Diet Items and Fatty Acids in the Cross-Sectional Oslo Health Study. Issue 4 (December 2014) - Høstmark, Arne Torbjørn; Haug, Anna; Holmboe-Ottesen, Gerd
Abstract Objectives: Antioxidants and a balanced ratio between Omega-3 and Omega-6 fatty acids may influence musculoskeletal pain, raising the question of whether pain is related to intake of particular food items. Methods: In the cross-sectional Oslo Health Study, including 18 770 men and women, there were 12 025 subjects with data on musculoskeletal pain, and on intake of various food items. We calculated the Sumpain index to estimate the extent/severity of pain. Using multiple linear regression models, we studied the association between Sumpain and diet items possibly related to pain. In addition, the Omega-3/Omega-6 fatty acid ratio in serum phospholipids was determined in 139 of the subjects; 84 ethnic Norwegians and 55 Pakistani immigrants. Results: Sumpain was negatively associated with intake of fruits/berries and fruit juice, when controlling for sex, age, smoking, body mass index, length of education, physical activity, and intake of coffee, alcohol, fruit juice, vegetables/salads, fatty fish, and cod liver oil. Sumpain was higher in women than in men, and was negatively associated with intake of alcohol, length of education and physical activity, but was positively related to age, body mass index and smoking. The Omega-3/Omega-6 fatty acid ratio in serum phospholipids was negatively associated with Sumpain, and was lower in the immigrant group, which had a higher mean Sumpain score. Conclusions: The results raise the question of whether intake of fruits/berries, fruit juice, and a balanced fatty acid pattern in serum phospholipids, might protect against musculoskeletal pain.